2019
DOI: 10.1016/j.redox.2019.101179
|View full text |Cite
|
Sign up to set email alerts
|

Using resonance synchronous spectroscopy to characterize the reactivity and electrophilicity of biologically relevant sulfane sulfur

Abstract: Sulfane sulfur is common inside cells, playing both regulatory and antioxidant roles. However, there are unresolved issues about its chemistry and biochemistry. We report the discovery that reactive sulfane sulfur such as polysulfides and persulfides could be detected by using resonance synchronous spectroscopy (RS 2 ). With RS 2 , we showed that inorganic polysulfides at low concentrations were unstable with a half-life about 1 min under physiological conditions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 44 publications
(77 reference statements)
2
50
0
Order By: Relevance
“…Under the same conditions, parental reduced glutathione (GSH) or H 2 S failed to reduce H 2 O 2 [ 5 ]. Li et al reported that GSSH was 50-fold more reactive than was H 2 S toward H 2 O 2 at physiological pH [ 46 ]. In cell systems, the overexpression of CSE enhanced GSSH levels and, more importantly, protected cells from H 2 O 2 -induced death [ 5 ].…”
Section: Antioxidative and Nucleophilic Properties Of Persulfides/mentioning
confidence: 99%
See 1 more Smart Citation
“…Under the same conditions, parental reduced glutathione (GSH) or H 2 S failed to reduce H 2 O 2 [ 5 ]. Li et al reported that GSSH was 50-fold more reactive than was H 2 S toward H 2 O 2 at physiological pH [ 46 ]. In cell systems, the overexpression of CSE enhanced GSSH levels and, more importantly, protected cells from H 2 O 2 -induced death [ 5 ].…”
Section: Antioxidative and Nucleophilic Properties Of Persulfides/mentioning
confidence: 99%
“…Persulfides are stronger acids than are thiols, so at physiological pH (at which many thiols occur predominantly in the protonated form), a significant proportion of hydropersulfide species exist as a deprotonated persulfide anion (RSS – ) [ 19 ]. In fact, Li et al recently reported that the p K a of GSSH was 6.9, that is, two orders of magnitude smaller than that of GSH (p K a = 8.9) [ 46 ]. RSS – , thus formed, readily reacted with radical species to form persulfide radicals (RSS•) [ 47 ].…”
Section: Antioxidative and Nucleophilic Properties Of Persulfides/mentioning
confidence: 99%
“…We used the linear equation to fit the data obtained from the psRFP-GSSH reaction. Parameters showed that the slope is 0.003 and the intercept is 0.4. psRFP showed higher sensitivity toward HS n H than GSSH, probably because HS n H is more active than GSSH [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cellular sulfane sulfur exists as hydrogen polysulfide (HS n H, n ≥ 2), organopolysulfide (RS n H, n ≥ 2), and dialkyl polysulfide (RS n R, n ≥ 3). They come in different reactivities with a rough order of HS n H > RS n H > RS n R [ 7 , 8 ]. HS n H and RS n H have both electrophilic and nucleophilic properties, and vividly react with reactive oxygen species (ROS), reactive nitrogen species (RNS), and signaling molecules at physiological pH (7.0~7.6).…”
Section: Introductionmentioning
confidence: 99%
“…Also very recently, it has been reported that sulfane sulfur, including that in polysulfides and persulfides, could be detected by using resonance synchronous spectroscopy (RS 2 ) (Li et al, 2019). Sulfane sulfur displayed species-specific RS 2 spectra.…”
Section: Sulfane Sulfur Quantification In Biological Samplesmentioning
confidence: 99%